(untitled) (Journal of Applied Learning and Teaching, 2019)
Purpose: This paper is extending the existing body of knowledge by adding a new conceptual framework around funding of curriculum development for education in the SaaS (Software as a Service) industry. Design/methodology/approach: This paper is investigating a new crowdsourcing curriculum development approach that is currently rolled out by one large SaaS vendor (IBM) to understand their solution. Based on literature research, the key properties of ‘crowds’ will be identified. The literature review is, in addition, giving an overview on how the new approach fits to existing knowledge. Findings: The current research will differentiate the new approach from existing solutions in the literature and provide a suggestion for categories helping companies to understand the differences or similarities to other approaches. Originality/Value: This study is building the conceptual framework of a model outlining multiple approaches for funding for curriculum development with the help of a crowd.